Recent Advancements in Development and Therapeutic Applications of Genome-Targeting Triplex-Forming Oligonucleotides and Peptide Nucleic Acids - Yu Mikame; Asako Yamayoshi (MDPI AG, 2023)
Recent developments in artificial nucleic acid and drug delivery systems present possibilities for the symbiotic engineering of therapeutic oligonucleotides, such as antisense oligonucleotides (ASOs) and small interfering ribonucleic acids (siRNAs). Employing these technologies, triplex-forming oligonucleotides (TFOs) or peptide nucleic acids (PNAs) can be applied to the development of symbiotic genome-targeting tools as well as a new class of oligonucleotide drugs, which offer conceptual advantages over antisense as the antigene target generally comprises two gene copies per cell rather than multiple copies of mRNA that are being continually transcribed. Further, genome editing by TFOs or PNAs induces permanent changes in the pathological genes, thus facilitating the complete cure of diseases. Nuclease-based gene-editing tools, such as zinc fingers, CRISPR-Cas9, and TALENs, are being explored for therapeutic applications, although their potential off-target, cytotoxic, and/or immunogenic effects may hinder their in vivo applications. Therefore, this review is aimed at describing the ongoing progress in TFO and PNA technologies, which can be symbiotic genome-targeting tools that will cause a near-future paradigm shift in drug development.